Performance Investigation of Underwater Retroreflective Optical Integrated Sensing and Communication System - WAN Xin; WANG Haochuan; YE Yang; ZENG Zhihong; LIU Min; LENG Min; CHEN Chen (Guangtongxin yanjiu)
【Objective】Lightwave-based Retroreflective Optical Integrated Sensing and Communication (RO-ISAC) systems have the advantages of large communication capacity and high sensing accuracy, which can offer communication and sensing capabilities for the underwater activities. However, the limited Field of View (FOV) of the Corner Cube Reflector (CCR) in underwater RO-ISAC systems greatly limits the effective sensing range of the system. Hence, how to increase the FOV of the CCR to expand the effective sensing range of the system is a subject that needs to be solved urgently. Moreover, the impact of underwater turbulence on the communication and sensing performance of the RO-ISAC system also remains to be further explored.【Methods】For the limited FOV issue of the CCR, we propose a CCR array scheme based on an angle diversity structure. The proposed angle diversity CCR array consists of a central CCR unit and multiple side CCR units distributed in a circle, where each side CCR unit has a certain tilt angle. In the underwater RO-ISAC system based on the angle diversity CCR array, Orthogonal Frequency Division Multiplexing (OFDM) is adopted as the ISAC waveform, and the communication and sensing performance of the RO-ISAC system in the underwater turbulence channel is studied through Matlab software simulation.【Results】Simulation results show that, under the condition of the same equivalent reflection area, the angle diversity CCR array can significantly increase the FOV of the CCR. Moreover, as the number of side CCR units in the angle diversity CCR array increases, the equivalent FOV also increases, and the sensing (i.e., ranging) performance of the underwater RO-ISAC system improves accordingly. At the same time, there is an optimal interval for the tilt angle of the side CCR units in the angle diversity CCR array, which is highly related to the incident angle of the optical signal. In addition, in the underwater RO-ISAC system based on the OFDM waveform, underwater turbulence has a great impact on the Bit Error Rate (BER) performance of the system. When the turbulence is stronger, the BER performance is worse. In contrast, underwater turbulence has no obvious impact on the ranging performance of the system.【Conclusion】The proposed angle diversity CCR array can significantly expand the effective sensing range of the under-water RO-ISAC system and improve the sensing accuracy. At the same time, the underwater RO-ISAC system based on the OFDM waveform can effectively overcome the adverse effects of underwater turbulence on the sensing performance.